ANALISIS POLA OPERASI WADUK SANGIRAN - Maulana, Rifki; Hadiani, Rr Rintis; Ikhsan, Cahyono (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2020)
Dam is a reservoir that is needed to save water so that it can be used at the time needed both for irrigation, hydropower, and tourism. One of the Functional Dam in Indonesia is the Sangiran Dam. Sangiran Dam is located in Sumber Bening Village, Bringin District, Ngawi Regency, East Java Province. The Sangiran Dam is equipped with an overflow ogee crest type overflow building with side channels. Sangiran Dam gate type is slide gate with automatic operation using electric generator. The reservoir, which was operated starting in 2000, is designed to meet the needs of a plantation area of 1535 ha. However, in the operation that is needed in meeting the needs of irrigation air needs to be done in research the current operating patterns of the operating patterns that have been designed at the time of the reservoir design to compile an operating pattern that can meet water needs, at this time, looking for a relation between the elevation of reservoir water levels with an outflow discharge coming out of the reservoir. Based on the results of the analysis conducted on the current operating patterns are not in accordance with the pattern of initial design operations with an average deviation of 51.78% per year. This research is being carried out to analyze the optimal operating patterns of the Sangiran Dam and / or possible operating patterns in meeting water needs in the following years.